State-dependent fiscal multipliers and financial dynamics: An impulse response analysis by local projections for South Africa - Serena Merrino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
The aim of this paper is to assess South Africa's fiscal multiplier across different states of the economy, with a focus on the financial accelerator mechanism of fiscal policy shocks, by estimating impulse response functions from both linear and non-linear local projections. The model finds evidence of strong business cycle effects such that, while the average multiplier is below 0.5, it reaches 1.2 during recessions and that, while credit volume diminishes during periods of positive output gap, it expands otherwise. Results suggest that a fiscal expansion crowds out private economic activity in good times only, while it holds a positive balance-sheet effect on liquidity-constrained agents during bad times. Evidence of a state-dependent financial accelerator mechanism of fiscal expansion is confirmed by the positive response of the Financial Times Stock Exchange/Johannesburg Stock Exchange All-Share Index during times of slack.
Keywords: C32; E44; E62; 330; fiscal multiplier; local projections; state-dependent multiplier; credit; South Africa